Indigenous peoples' wisdom and power affirming our knowledge through narratives - Kunnie, Julian E.; Goduka, Nomalungelo I. (Nomalungelo Ivy) 1948- (Vitality of indigenous religions, 2016)
Indigenous scholars are reviving the art and science of storytelling as a means of transmitting layers of meaning to accounts of spirituality, culture, cognition and control. In this collection of 16 studies from around the world, contributors present their work in ancient cultures, Turtle Island (North America), South America, the Caribbean, the Pacific, Asia, Europe and Africa. Topics include indigenous knowledge and survival struggles, knowledge systems, indigenous research, naming and identity in colonization, oral tradition, indigenous healing, women at work, wisdom in ancestral cults, sacred and spiritual wisdom, resilience and resistance, ecological citizenship, indigenous journeys in Europe, indigenous views as tools of development, panegyric legends, human rights and globalization. Annotation ©2006 Book News, Inc., Portland, OR (booknews.com)